Long-term detoxification of opioid use disorder with opium tincture assisted treatment - Omidvar Tehrani, Sahar; Rezaei Ardani, Amir; Akhlaghi, Saeed; Shayesteh Zarrin, Masood; Talaei, Ali (Frontiers in Psychiatry, 2023)
Introduction Retention in treatment, craving, and relapse rate are important indicators of the success rate in addiction maintenance therapy as they evaluate the effectiveness of the therapy and make necessary adjustments to the treatment plan. However, the rate of continuation in the treatment process and the rate of craving in patients with opioid use disorder undergoing maintenance treatment with opium tincture have not been studied. The present study aimed to investigate the rate of relapse, craving, and psychiatric disorders in patients with opioid use disorder undergoing treatment of gradual detoxification with opium tincture. Methods Ninety patients with opioid use disorder who underwent treatment with the gradual detoxification method using opium tincture in the form of Congress 60 for 11 months were enrolled in the study. The level of craving based on the Desire for Drug Questionnaire (DDQ) and patients’ self-report of drug use, the level of anxiety, depression, and sleep quality of patients were evaluated using the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and Pittsburgh Sleep Quality Index (PSQI), respectively. Also, suicidal thoughts were assessed by Beck Scale for Suicidal Ideation and quality of life by the World Health Organization Quality of Life Questionnaire (WHOQOL-BREF). Results The study found that the treatment resulted in a relapse rate of 16.7% for relapse. We also found that all sub-scales of the desire for drug questionnaire (DDQ), depression, and anxiety were significantly lower at the end of the study compared to its beginning. Additionally, quality of life and sleep significantly increased at the end of the study. All areas of craving, anxiety, and depression significantly decreased in all follow-up sessions that took place 1, 5, and 11 months after the start of treatment. Moreover, sleep disorders were improved considerably at the end of the treatment. Conclusion The current study presented a low relapse rate of Iranian patients with opioid use disorder under structured treatment of gradual detoxification with opium tincture in a one-year follow-up period. Opium tincture under the Congress 60 protocol may help to control carving, decrease psychological disorders, improve quality of life, and consequently, lower relapse rate.